2007
DOI: 10.1111/j.1530-0277.2007.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone Is Associated With Reduced Drinking by Alcohol Dependent Patients Receiving Antidepressants for Mood and Anxiety Symptoms: Results From VA Cooperative Study No. 425, “Naltrexone in the Treatment of Alcoholism”

Abstract: Further investigation will be needed to determine whether naltrexone is efficacious among depressed alcohol dependent patients and whether naltrexone and antidepressant medications show interactive efficacy for treating alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
(33 reference statements)
0
10
0
1
Order By: Relevance
“…The impact of depressive symptoms or depression on naltrexone's effectiveness is not clear, with evidence from some trials suggesting their presence is associated with greater improvements (Kiefer et al, 2003;Krystal et al, 2008;Morley et al, 2010) Naltrexone + psychosocial interventions. The interaction between a number of different psychosocial interventions and naltrexone has been investigated, with no clear advantage of one approach.…”
Section: (Ib)mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of depressive symptoms or depression on naltrexone's effectiveness is not clear, with evidence from some trials suggesting their presence is associated with greater improvements (Kiefer et al, 2003;Krystal et al, 2008;Morley et al, 2010) Naltrexone + psychosocial interventions. The interaction between a number of different psychosocial interventions and naltrexone has been investigated, with no clear advantage of one approach.…”
Section: (Ib)mentioning
confidence: 99%
“…Therefore naltrexone and disulfiram can be used safely in depressed alcoholics with comparable efficacy with those not depressed. Krystal et al (2008) (Ib) undertook a secondary analysis of the VA naltrexone trial where naltrexone failed to show significant advantage over placebo. During the study, about 10% of people required antidepressants since their mood worsened.…”
Section: Relapse Prevention Medication In Depressionmentioning
confidence: 99%
“…For example, several studies have examined the impact of the opioid antagonist medication naltrexone and the SSRI medication, sertraline. 44, 45, 46, 47 These studies suggest that the combination treatment can lead to higher rates of abstinence from alcohol, longer time to drinking relapse, and improvement in mood relative to those who receive either placebo or antidepressant or AUD pharmacologic interventions alone.…”
Section: Treatment Challengesmentioning
confidence: 98%
“…A secondary analysis of a randomized trial of naltrexone or placebo for military veterans with alcohol dependence found that the addition of SSRIs among those who developed worsening anxiety or depressive symptoms during the trial did not negatively impact the efficacy of naltrexone for alcohol outcomes. 83 …”
Section: Treatments Targeting the Substance Use Disordermentioning
confidence: 99%